A hidden life [videorecording (DVD)] - Malick, Terrence, 1943-; Diehl, August, 1976-; Pachner, Valerie, 1987-; Simon, Maria, 1976- (Twentieth Century Fox Home Entertainment, 2020)
Based on real events, this is the story of an unsung hero, Franz Jägerstätter, who refused to fight for the Nazis in World War II. When the Austrian peasant farmer is faced with the threat of execution for treason, it is his unwavering faith and his love for his wife Fani and children that keep his spirit alive.